An Albino Muskox near the Atkinson Point River, Northwest Territories - Kuyt, E.; Schroeder, C.H.; Brazda, A.R. (ARCTIC, 1972)
Gavin during his stay near the mouth of the Perry River (67°48'N, 102°16'W) from 1937-1941 reported only few muskoxen. The largest herds were 12 and 15, seen in 1938 on the mainland a few miles west of the mouth of the Perry River. Aleksiuk saw no muskoxen during his period of field work in the Perry River area from 21 May to 10 August 1963 but reported that, according to local Eskimos, muskoxen were still found in the region of MacAlpine Lake, at the headwaters of Perry River. During waterfowl surveys on 11, 15, and 16 August 1971, between Perry River and the Atkinson Point River (103°18'W) and between 67°10'N and 67°45'N we saw the following numbers of muskoxen: 1, 26, 48, 1, 1, 23, 16, 1, 1. Dates of observation of herds, their location and numbers of yearlings preclude the possibility of duplication. Of particular interest was the occurrence of a light-coloured individual in the herd of 23 observed on 15 August along the Atkinson Point River at 67°45'N, 103°18'W. The animal in question was a large adult of a pale creamy-yellow colour. Photographs taken at the time show the animal to be accompanied by a yearling of normal colouration. At first the pale-coloured individual was thought to be a bull but the persistent proximity of the yearling and the adult's behaviour in running at the forefront of the herd when chased (in opposition to bulls which normally follow the herd) suggested that the muskox in question was a cow. We were unable to get a good look at the cow's horns but they appeared paler than in muskoxen having the typical pelage; just then we had run into low cloud and rain and were in fact retreating to our camp on the Perry River. Only one albino muskox has been recorded previously. Tener quotes McDougall's observation of an adult albino cow muskox on 18 June 1853 at Cape Smyth, Melville Island. That cow was followed by a black calf.